Possibility of Usingdata Satellite Forestimate of Forage Production (Indonesian Animal Sciences Society, 1999)
One of factors to analyse carrying capacity for ruminant of one area is to calculate the forage potency which includes grasses, leave and agricultural by-product. Estimation of forage potency is affected by agroclimate variation, type and land topography and traditional agricultural system . The data availability on forage potency of one area usually is very limited so that the accuracy on area potency will also be low. Remote sensing technique using LANDSAT satellite managed by LAPAN could provide satellite image data on a specific area . 1lvough interpretation of satellite image data by hard and softwares, supported by topography map, thematic map, and agricultural statistic data, forage potency on one area could be analysed quicker and more accurate. Based on forage potency, carrying capacity ofone area can be determined . Key words : Satellite data, production of forage